New Insights and Perspectives on Intrarenal Renin-Angiotensin System: Focus on Intracrine/Intracellular Angiotensin II() - Zhuo, Jia L. (2011)
Although renin, the rate-limiting enzyme of the renin-angiotensin system (RAS), was first discovered by Robert Tigerstedt and Bergman more than a century ago, the research on the RAS still remains stronger than ever. The RAS, once considered to be an endocrine system, is now widely recognized as dual (circulating and local/tissue) or multiple hormonal systems (endocrine, paracrine and intracrine). In addition to the classical renin/angiotensin I-converting enzyme (ACE)/angiotensin II (Ang II)/Ang II receptor (AT(1)/AT(2)) axis, the prorenin/(Pro)renin receptor (PRR)/MAP kinase axis, the ACE2/Ang (1-7)/Mas receptor axis, and the Ang IV/AT(4)/insulin-regulated aminopeptidase (IRAP) axis have recently been discovered. Furthermore, the roles of the evolving RAS have been extended far beyond blood pressure control, aldosterone synthesis, and body fluid and electrolyte homeostasis. Indeed, novel actions and underlying signaling mechanisms for each member of the RAS in physiology and diseases are continuously uncovered. However, many challenges still remain in the RAS research field despite of more than one century's research effort. It is expected that the research on the expanded RAS will continue to play a prominent role in cardiovascular, renal and hypertension research. The purpose of this article is to review the progress recently being made in the RAS research, with special emphasis on the local RAS in the kidney and the newly discovered prorenin/PRR/MAP kinase axis, the ACE2/Ang (1-7)/Mas receptor axis, the Ang IV/AT(4)/IRAP axis, and intracrine/intracellular Ang II. The improved knowledge of the expanded RAS will help us better understand how the classical renin/ACE/Ang II/AT(1) receptor axis, extracellular and/or intracellular origin, interacts with other novel RAS axes to regulate blood pressure and cardiovascular and kidney function in both physiological and diseased states.